Вплив пандемічної кризи на систему маркетингу дрібнотоварних виробників сільськогосподарської продукції в Україні - Самофал, О. В.; Samofal, O. (Дніпровський державний аграрно-економічний університет, 2021)
Статтю присвячено вивченню впливу пандемічної кризи на систему маркетингу дрібнотоварних виробників сільськогосподарської продукції в Україні. Охарактеризовано актуальний критичний стан таких виробників сільськогосподарської продукції внаслідок довготривалого впливу сучасної пандемії та антипандемічних заходів, які були розроблені з метою зниження кількості соціальних контактів. Проведено опитування власників особистих селянських господарств та малих фермерських господарств з різноманітною спеціалізацією з метою встановлення основних наслідків, яких вони зазнають. Виявлено, що найбільше такі виробники страждають від обмежувальних адміністративних заходів, зокрема, закриття ринків та ярмарок, де вони звикли реалізовувати дрібні партії продукції. Запропоновано шляхи мінімізації таких наслідків та рекомендовано базові орієнтири формування маркетингової політики виходу з постпандемічної кризи для українських дрібнотоварних виробників сільськогосподарської продукції. The article is about studying the impact of pandemic crisis on the marketing of small-scale agricultural producers in Ukraine. The current critical condition of such agricultural producers due to the long-term impact of the modern pandemic and anti-pandemic measures have been developed to reduce the number of social contacts is described. A survey of owners of private and small-scale farms with different specialization to establish pandemic effects they experience has been conducted. It was established that such producers mostly suffer because of restrictive administrative measures, including the closure of markets and fairs, where they used to sell small batches of their products. The forced reduction of social contacts, the outflow of resources for administrative measures related to the prevention and treatment of diseases, the introduction of partial or complete cessation of business activities in retail and restaurant business have led to a sharp decline in sales of agricultural products. In order to study the impact of the pandemic crisis on the activities of small-scale agricultural production in Ukraine and the world, a study was conducted, which consisted of two stages. The first stage is an analytical review of scientific and statistical publications by Ukrainian and foreign authors on the problems of the current impact of the pandemic on the economy of small-scale agriculture. The second stage of the study is telephone interviews with 60 small farmers of various specializations from different regions in the East, West, South, North and Center of Ukraine. The sample of respondents was conducted through invitations with the help of local governments and activists. Summarizing the results of the farmers' survey, it is possible to identify the following elements of the negative impact of the pandemic crisis on the economic activity of small agricultural producers, in particular on its marketing component. The article proposed ways of minimizing these effects and recommended basic guidelines forming marketing policy out of the post pandemic crisis for small-scale Ukrainian agricultural producers.
The influence of the pandemic crisis on the marketing system of small-scale agricultural producers in Ukraine
Keywords: дрібнотоварні виробники; small-scale producers; сільськогосподарська продукція; agricultural products; маркетинг; marketing; пандемія; pandemic; криза; crisis; кооперація; cooperation